13b=-12+16b

Simple and best practice solution for 13b=-12+16b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13b=-12+16b equation:


Simplifying
13b = -12 + 16b

Solving
13b = -12 + 16b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-16b' to each side of the equation.
13b + -16b = -12 + 16b + -16b

Combine like terms: 13b + -16b = -3b
-3b = -12 + 16b + -16b

Combine like terms: 16b + -16b = 0
-3b = -12 + 0
-3b = -12

Divide each side by '-3'.
b = 4

Simplifying
b = 4

See similar equations:

| 7+6(1w-3)=31 | | -v-10=10-6v | | 5j-10+9j=5+9j | | -14+3x=x | | 6a+7b=19 | | 3x-10=2x+20 | | 5(1a-4)=44 | | 4s=5s+6 | | 3(x-2)=2x+3+x | | X^2-25x+256=0 | | 18=2[x+6] | | 10p=6+7p | | 5x+50=-95 | | g+10=-9g | | a=15-b | | 8n-10=10n+10 | | x=-27+-2.25y | | ab=56 | | 3x-4+2y= | | 2(a-2)=49(2a-4) | | (2x+6)+(2x+5)+(2x)=(2x)+(2x)+(3x+2) | | -3q-8=10-5q | | -8z+8=-7z | | 1t^2-300t+45000= | | 8g+41=6g+95 | | 3(y+4)+2=29 | | 1.8+2.5= | | 4s-10=6s | | 4(5x+2)=Y | | 10-3u=-5u-4 | | 4(x-1)+2x=6(x-6) | | 4s+7t=79 |

Equations solver categories